Effect of Food Consumption Modification through DASH Diet Program amongst Risk Group to Prevent Hypertension, Nabon District, Nakhon Si Thammarat Province - คงแก้ว นริศรา; ชัยขันธ์ อนุธิดา; สุวรรณคง ดุษณีย์; บุญรอด ตั้ม (Journal of Health Science of Thailand, 2022)
This quasi - experimental study aimed to determine the effect of food consumption modification through DASH diet program amongst risk group to prevent new hypertension case, Nabon district, Nakhon Si Thammarat province. The sample were 72 hypertension risk subjects. Simple random sampling was used and divined into experimental and control groups: 36 each. Such diet program was carried out for nine weeks based on motivation theory and social support theory. The experimental group was provided DASH diet program: (1) promoting perceived severity and risk to hypertension; (2) advocating response efficacy and self-efficacy to disease prevention; (3) encouraging DASH diet practice; (4) sharing experiences with successful person who can control blood pressure well, and (5) visiting person at his/her home. The data was analyzed using descriptive and inferential statistics. It revealed that perceived severity of disease, perceived probability of disease, response efficacy and self-efficacy were statistically significant (p<0.05). Social support was not significantly difference (p>0.05) between experimental and control groups. Blood pressure level between two groups were significantly difference (p<0.05). Thus, health care providers in the locality should promote risk group to adapt consumption behavior style following DASH diet program continually to reduce new hypertension cases in the community.